2015
DOI: 10.1590/0103-8478cr20150348
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento amostral para a estimação da média de precipitação pluvial mensal em locais do Estado do Mato Grosso do Sul

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
4
0
1
Order By: Relevance
“…Given these high percentages with fit to normal distribution, it can be concluded that the use of normal distribution has credibility for estimating the monthly rainfall in the Mato Grosso do Sul State, agreeing with the results obtained by Torres et al (2016). The greatest probable precipitation values at 75% probability by normal distribution occurred between the months of November to April, which allows us to classify these months as the rainiest months of the year in Mato Grosso do Sul (Figure 1).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Given these high percentages with fit to normal distribution, it can be concluded that the use of normal distribution has credibility for estimating the monthly rainfall in the Mato Grosso do Sul State, agreeing with the results obtained by Torres et al (2016). The greatest probable precipitation values at 75% probability by normal distribution occurred between the months of November to April, which allows us to classify these months as the rainiest months of the year in Mato Grosso do Sul (Figure 1).…”
Section: Resultssupporting
confidence: 84%
“…Probable rainfall was estimated at 75% probability, using the normal probability distribution according Torres et al (2016), also named Gaussian curve, which shows two parameters and its probability density function is defined by the equation (HASTINGS;PEACOCK, 1975):…”
Section: Estimate Of the Probable Rainfallmentioning
confidence: 99%
“…The Brazilian State of Mato Grosso do Sul plays a significant role in the national agriculture where information on rainfall is of vital importance (Correa et al ., 2014; Teodoro et al ., 2016; Torres et al ., 2016). Approximately 65% of the area of Pantanal, a particular and important biome and the largest continental wetland in the world (Ioris et al ., 2014), is located in the northwest of the state.…”
Section: Introductionmentioning
confidence: 99%
“…De maneira geral, dentre os elementos climáticos, é possível observar que a precipitação é o elemento que possui menor precisão das estimativas tomando como base trinta anos de observação (Cargnelutti Filho et al, 2009). Um estudo recente observou que trinta anos são suficientes para prever a precipitação na maioria dos meses do ano, com exceção de junho, julho e agosto, uma vez que para esses meses podem ser necessários até sessenta e três anos (Torres et al, 2016).…”
Section: Introductionunclassified